Auditoría en seguridad vial, tramo vial Alcalá – Pereira, tramos del Km 0+000 hasta Km 5+200 y Km 11+200 hasta el Km 15+000 - Gutiérrez Arias, Laura Valentina; Londoño Hincapié, Yudy Alexandra; Muñoz Padilla, Alejandra (Universidad Antonio Nariño, 2023)
In this work, the Road Safety Audit was developed for the section via Alcalá - Pereira, sections from Km 0+000 to Km 5+200 and Km 11+200 to Km 15+000, signaling, vehicle containment barriers and design. geometry that make up the road, to determine its condition in front of the road actors that circulate through it, to determine the accident rate in the aforementioned. For this, the quantitative methodology was used, the operationalization of the objectives was carried out and through data collection instruments such as risk matrices.